Economies of Obedience II - Bubakar Sal; Malcolm Diarra (The Pan African Sovereign Network, 2025)
This article tests a psychopolitical model of imperial selection against the recent trajectory of the Democratic Republic of Congo (DRC). A 2018 paper by Kusimbiko proposed the Imperial Selection Model (ISM) and a Trait-System Fit Index (TSFI), arguing that postcolonial decline is driven less by “culture” and more by the psychological structure of leadership and its fit with imperial interests. The original model forecast that, if a high-TSFI leadership were installed in Kinshasa, the DRC would experience rapid re-entry into IMF programmes, a three-fold currency collapse within five to six years, several million excess deaths from systemic neglect, and highly asymmetric, Western-aligned resource deals backed by diplomatic protection. Using macroeconomic series, excess-mortality estimates, official documents on the 2025 U.S.–DRC Strategic Partnership Agreement, and independent reporting on the Lobito Corridor, this article compares those predictions with the actual evolution of DRC governance between 2019 and 2025. The match is unusually strong for political science. The regime’s external alignment, debt trajectory, devaluation of the Congolese franc, and the structure of the new critical-minerals agreements all follow the pattern that ISM described as “puppet governance” and “economies of obedience.” The article refines the model in three ways. First, it states explicit falsification criteria: a regime that normalises carelessness toward its own population but does not produce elevated neglect-related excess mortality would falsify the current formulation. Second, it clarifies ethics and scope: the ISM pathologises policies and ruling styles, not the private moral worth of individuals. Third, it proposes upgrades to the Puppet Diagnostic Index (PDI), including a “carelessness test” based on basic public-goods indicators and a clearer coding of sovereignty-erosion events such as mining and corridor treaties. The article concludes that the DRC sequence of 2019–2025 offers a rare real-time validation of a psychopolitical model and underlines the need for preventive diagnostics before new high-TSFI leaders are selected.
Real-Time Validation of Puppet Governance in the DRC, 2019–2025